DAMPAK PEMANFAATAN KONTEN DIGITAL TIKTOK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP RELIGIOSITAS SISWA SMA - Wahdah; Imran, Yusida; Alias, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine The Impact of Utilizing TikTok Digital Content in Islamic Religious Education Learning on High School Students' religiosity. The research is grounded in the growing integration of digital technology in education and the increasing exposure of adolescents to online religious content. The aim is to determine how digital learning materials contribute to the development of students’ religiosity. Employing a quantitative approach with an explanatory research design, data were collected through Likert-scale questionnaires, classroom observations, and documentation, and were analyzed using parametric statistical tests via SPSS. The findings indicate that both digital content utilization and students’ religiosity are categorized as high. The reliability test yielded a Cronbach’s Alpha of 0.786, while simple linear regression revealed a positive and significant effect of digital content use on students’ religiosity (R = 0.657; R² = 0.432; p < 0.05). This means that 43.2% of the variance in students’ religiosity is explained by their engagement with digital PAI content. The study contributes to the literature on digitalization in Islamic education and offers practical implications for educators to optimize credible and pedagogically sound digital materials to strengthen students’ religious character.